Ceacal perforation in a premature newborn infant complicating milk curd syndrome: Case report - Aytaç KARKINER; Günyüz TEMİR and Münevver HOŞGÖR and Cüneyt GÜNŞAR and İrfan KARACA (Turkish Journal of Gastroenterology, 2019)
-